(3JQbjI GdehXa GdYGe HOhdI bWQ (B: s (3OQGSI ebGQfI (B/ s - (3CMeO eMeO MSf GdMji GdSdjWjs; (3CfhQ CMeO QSdGf (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2005)
(3dbO MXi ehVhY JQbjI GdehXa GdYGe HeRjO ef GdYfGjI hGdGgJeGe ai Xd eG JTgOg GdOhd eMd GdOQGSI ef JbOe hJWhQ ai GdfXe GdGbJUGOjI hGdGLJeGYjI hGdJTQjYjI hdeG cGf GdaQO HWHjYJg cGFfG GLJeGYjG dG jYjT ai GdeLJeY eY GaQGO eKdg Phi ehGgH eJHGjfI hGSJYOGOGJ eMOhOI (B: (3HMjK dG jSJWjY Gf jfJL HfaSg dhGRe GdMjGI hebJVjGJ GdeYjTI (B: (3acGf dGHO dg ef GdJYGhf eY Hfi fhYg ddMUhd HWQjb GdJHGOd Ydi dhGRe GdMjGI GdJi dG jJjSQ dg GdHbGA HOhfgG (B: (3hGdOhdI gjFI GLJeGYjI Jbhe HGOGA NOeGJ eYjfg heUGdM eTJQcI ddGaQGO hGdLeGYGJ GdechfI ddGeI GdJi JeKdgG GdOhdIs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2005.s
(3HHdjhLQGajG(B: (3UaMGJ(B426 -444.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdehXa GdYGes; (3GdeQcR GdbGfhfj ddehXa GdYGe aj eUQ hbWQ hHQjWGfjGs; (3GdJQbjIs; (3ehGfY GdJQbjIs; (3GdQbGHI Ydi bQGQGJ GdJQbjIs; (3GdLRGAGJ GdJCOjHjIs; (3GdehXa GdYGes; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2005